Okul öncesi dönem çocuklarının ego sağlamlık düzeylerinin incelenmesi - BALABAN DAĞAL, ASUDE (My University, 2018)
Ego sağlamlığı risk faktörlerine rağmen olumlu gelişme eğilimi olarak tanımlanmaktadır.Çocuğun gelişimi açısından risk oluşturan faktörler ve bu risk faktörlerine rağmen gelişimini olumludevam ettirebilmesine olanak veren koruyucu faktörler bireysel, ailesel ve çevresel boyutta elealınmaktadır (Brown, Barbarin ve Scott, 2013; Gizir 2007). Okul öncesi dönem çocuklarla egosağlamlık düzeyini etkileyen değişkenleri inceleyen Türkiye’deki araştırma sayısı oldukça sınırlıdır.Bu nedenle araştırmanın amacı, 50-72 aylık, okul öncesi eğitim kurumlarına devam etmekte olançocukların ego sağlamlık düzeylerinin yaşlarına, cinsiyetlerine, anne-baba yaşlarına, anne-babaeğitim düzeyine, sahip oldukları kardeş sayılarına ve evde bakıcı olup olmamasına göre farklılaşıpfarklılaşmadığını tespit etmek olarak belirlenmiştir. Araştırma betimsel tarama modelindetasarlanmıştır. Veriler 2015-2016 eğitim-öğretim yılında, okul öncesi eğitim kurumlarına devameden çocukların annelerinden toplanmıştır. Araştırmada yaş ortalaması 65.03 ay olan 775 çocuğaulaşılmıştır. Araştırmaya katılan çocukların 397’si kız 378’i ise erkektir. Araştırmada veri toplamaaracı olarak Eisenberg ve arkadaşları tarafından 1996 yılında geliştirilen ve Önder ve GülayOgelman (2011) tarafından Türkçe’ye uyarlanan Ego Sağlamlığı Ölçeği (Anne Formu)kullanılmıştır. Araştırma sonuçlarına göre çocukların ego sağlamlık düzeyleri cinsiyet açısındandeğerlendirildiğinde kızlar lehine anlamlı bir fark elde edilmiştir. Diğer değişkenlerin ego sağlamlıkdüzeyi üzerindeki etkisi ise istatistiksel olarak anlamlı bulunmamıştır.

Ego resiliency is defined as positive development tendency despite risk factors. Factors that constitute a risk for the development of the child and protective factors that enable the development to continue in spite of these risk factors are considered at the individual, familiar and environmental dimensions (Brown, Barbarine and Scott, 2013; Gizir, 2007). Since the number of studies examining the variableEgo resiliency is defined as positive development tendency despite risk factors. Factors that constitute a risk for the development of the child and protective factors that enable the development to continue in spite of these risk factors are considered at the individual, familiar and environmental dimensions (Brown, Barbarine and Scott, 2013; Gizir, 2007). Since the number of studies examining the variables affecting ego resiliency with preschool children is limited in the relevant Turkish literature, the aim of this research is to determine the ego resiliency levels of the 50-72 months old children who are attending in preschool according to age, gender they attend, , ages of their parents, education level of the parents, the number of brothers/sisters they have and presence of a care giver. The research was designed in a descriptive survey model. The data were collected from children’s mothers who were attending preschool education institutions in the academic year of 2015-2016. 775 children with a mean age of 65.03 were reached in the survey. 397 girls and 378 girls are participating in the research. The Ego Resiliency Scale (Mother Form) that was developed by Eisenberg and her collegues in 1996 and adapted into Turkish by Önder and Ogelman (2011) was used as data collection tool in the study. According to the results of the research, when the ego resiliency levels were evaluated in terms of gender, it was found meaningful in favor of the girls. However, the ego resiliency of children does not differ statistically according to other variables.s affecting ego resiliency with preschool children is limited in the relevant Turkish literature, the aim of this research is to determine the ego resiliency levels of the 50-72 months old children who are attending in preschool according to age, gender they attend, , ages of their parents, education level of the parents, the number of brothers/sisters they have and presence of a care giver. The research was designed in a descriptive survey model. The data were collected from children’s mothers who were attending preschool education institutions in the academic year of 2015-2016. 775 children with a mean age of 65.03 were reached in the survey. 397 girls and 378 girls are participating in the research. The Ego Resiliency Scale (Mother Form) that was developed by Eisenberg and her collegues in 1996 and adapted into Turkish by Önder and Ogelman (2011) was used as data collection tool in the study. According to the results of the research, when the ego resiliency levels were evaluated in terms of gender, it was found meaningful in favor of the girls. However, the ego resiliency of children does not differ statistically according to other variables.
The investigation of the level of ego resilience of preschool children
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Aile Çalışmaları; Sosyal Çalışma